Desenvolvimento de novos complexos de íons Al3+ e Ga3+ contendo ligantes B-dicetonatos utilizados como camada emissora em OLEDs: estudo experimental e teórico - Costa, Israel Ferreira da (2019)
The present work reports the synthesis, characterization and studies of different photoluminescent and electroluminescent properties of Al3+ and Ga3+ ion compounds containing cyclic B-dicetonate ligands 2-acyl-1,3-indandionates (acind) and 2-acyl-1-indanonates(ind): 2-acetyl-1,3-indandionate (aind), 2-propyl-1,3-indandionate (propind), 2-benzoyl-1,3-indandionate (bind), 2-(4-methyl-phenyl)-1,3-indandionate (mbind) and 2-naphthyl-1,3-indandionate (nind), 2-acetyl- 1-indanonate (aci), 2-(2,2,2-Trifluoroethyl)-1-indanonate (tfi), 2-benzoyl-1-indanonate (bzi). Al3+ and Ga3+ complexes were synthesized by the irect reaction between the salts (chlorides or nitrates) of these ions with the indandionate ligands. All ligands and complexes were characterized by elemental analysis (CHN), Infrared Spectroscopy, 1H and 13C nuclear magnetic resonance and Thermogravimetric Analysis (TGA/DSC). The photophysical properties of the Al3+ and Ga3+ complexes in the powder and thin film forms were investigated from spectral absorption data in the UV-vis region and emission spectra recorded at room temperature (300K) and liquid nitrogen (77K). The obtained data demonstrated that these complexes exhibit luminescent properties similar to those for the Alq3 complex (aluminum tris-hydroxyquinolinate), which is widely used in electroluminescent devices as the emitter and electron carrier layer. However, the electronic properties of these compounds are significantly different from those presented by this reference complex. In this context, new electroluminescent devices were developed, with different architecture in which the complexes [Al(acind)3] and [Al(ind)3] were used as emitter layers and electron carrier in Molecular Devices (DMCL) of the OLED type. These devices were fabricated by thermal evaporation deposition in two different configurations: ITO/ B-NPB/[Al(acind)3]/LiF/Al (1) and ITO/ B-NPB/spiro-2CBP/[Al(acind)3]/Al(2), and ITO/B -NPB/[Al(ind)3]/LiF/Al. The bilayer devices exhibited red lectroluminescence, whereas the trilayer device exhibited green color. On the other hand, the device ITO/B -NPB/[Al(ind)3]/LiF/Al exhibited green color electroluminescence. The observed differences were correlated with the energy levels structures and the electrical properties of the compounds. The HOMO-LUMO energy levels and energy gap (Eopt) of the compounds were estimated based on the technique of cyclic voltammetry (CV) and optical absorption (UV-vis), respectively. The devices presenting (1) and (2) configurations were investigated based on the current-voltage characteristic (mA·m-2) and luminance (cd·m-2). The colors emitted by the compounds in the solid state and their devices were determined by the coordinates (x, y) of the CIE color diagram. Our results showed that it is possible tuning the emission color from green to red, in accordance with the change from the direct charge recombination in the emitting layer of the [Al(acind))3] complexes to an exciplex-based TADF emission in which [Al(acind))3] complexes and spiro 2-CBP acted as acceptor and donor, respectively. These results suggest that [Al(acind)3] complexes present great potential for applications in light-emitting systems for electronic displays and/or lighting. From theoretical perspectives, calculations based on the Functional Density Theory (DFT), the structures of the mer- and fac-[Al(aind)3] complexes were optimized using the B3LYP/6-31G (d) method. The excited state (spectroscopic) properties of the molecules were obtained by the time-dependent DFT theory (TD-DFT) employing different functionals (B3LYP, CAM-B3LYP, PBE1PBE, wB97XD e M06-2X). The results mainly of HOMO-LUMO showed good correlations with experimentally determined results